Appetite of an epiphyte: Quantitative monitoring of bacterial sugar consumption in the phyllosphere - Leveau, Johan H. J. (The National Academy of Sciences, 2001)
We report here the construction, characterization, and application of a bacterial bioreporter for fructose and sucrose that was designed to monitor the availability of these sugars to microbial colonizers of the phyllosphere. Plasmid pP(fruB)-gfp[AAV] carries the Escherichia coli fruB promoter upstream from the gfp[AAV] allele that codes for an unstable variant of green fluorescent protein (GFP). In Erwinia herbicola, this plasmid brings about the accumulation of GFP fluorescence in response to both fructose and sucrose. Cells of E. herbicola (pP(fruB)-gfp[AAV]) were sprayed onto bean plants, recovered from leaves at various time intervals after inoculation, and analyzed individually for GFP content by quantitative analysis of digital microscope images. We observed a positive correlation between single-cell GFP accumulation and ribosomal content as determined by fluorescence in situ hybridization, indicating that foliar growth of E. herbicola occurred at the expense of fructose and/or sucrose. One hour after inoculation, nearly all bioreporter cells appeared to be actively engaged in fructose consumption. This fraction dropped to approximately 11% after 7 h and to ≈1% a day after inoculation. This pattern suggests a highly heterogeneous availability of fructose to individual E. herbicola cells as they colonize the phyllosphere. We estimated that individual cells were exposed to local initial fructose abundances ranging from less than 0.15 pg fructose to more than 4.6 pg.